Quality Changes Of Red Chillia (Capsicum annum L.) During Cold Storage In Different Packaging - Bagas Surya Bawana; Lady C. C. E. Lengkey; Bertje R. A. Sumayku (Sam Ratulangi University, 2022)
Red chili is a horticultural product that is easily damaged so it cannot be stored for a long time. Physiologically, after being harvested red chilies continue to carry out metabolic activities such as respiration where the respiration rate depends on environmental conditions. To eliminate field heat during transportation, precooling is carried out with room cooling before storage and packaging. This respiratory activity cannot be stopped but can be reduced by storing it at low temperatures combined with proper packaging and stored at a temperature of 10.05 0C and 30.03 0C. with HDPE plastic clips, Wrapping LDPE based on quality changes. The research was conducted at the Agricultural Engineering Laboratory, Sam Ratulangi University, Manado from April to June 2022. This study used an experimental method, the data was processed descriptively. Performed 3 (three) plastic treatments with HDPE Clip, LDPE Wrapping and without packaging. Each treatment was repeated 3 times. This research was conducted at the Agricultural Engineering Laboratory, Sam Ratulangi University, Manado from April to May 2022. The results showed that red chilies packaged with LDPE wrapping could be stored longer (24 days) than those stored with HDPE plastic clips (21 days). Red chilies that are not packaged and stored at room temperature can only be stored for up to 6 days. Keywords: Capsicum anuum, Cold storage, Packaging.. Abstrak Cabai merah merupakan produk hortikultura yang mudah rusak sehingga tidak dapat disimpan dalam jangka waktu yang lama. Secara fisiologi, setelah dipanen cabai merah tetap melakukan kegiatan metabolisme seperti respirasi dimana laju respirasi ini tergantung dari kondisi lingkungannya. Untuk menghilangkan panas lapang saat pengangkutan dilakukan precooling dengan room cooling sebelum dilakukan penyimpanan dan pengemasan. Aktivitas respirasi ini tidak bisa dihentikan tetapi bisa dikurangi dengan melakukan cara penyimpanan pada suhu rendah yang dikombinasikan dengan pengemasan yang tepat.dan disimpan pada suhu 10,05 0C dan 30,03 0C Penelitian ini bertujuan untuk menentukan lama penyimpanan cabai merah yang disimpan dingin dan dikemas dengan plastik klip HDPE, Wrapping LDPE berdasarkan perubahan mutu. Penelitian dilakukan di Laboratorium Keteknikan Pertanian Universitas Sam Ratulangi Manado pada bulan April sampai Juni 2022. Penelitian ini menggunakan metode eksperimen, data diolah secara deskriptif. Dilakukan 3 (tiga) perlakuan plastik Klip HDPE, Wrapping LDPE dan Tanpa kemasan. Setiap perlakuan diulang 3 kali. Penelitian ini dilakukan di Laboratorium Keteknikan Pertanian Universitas Sam Ratulangi Manado pada bulan April sampai Mei 2022. Hasil penelitian menunjukkan bahwa cabai merah yang dikemas dengan wrapping LDPE dapat disimpan lebih lama (24 hari) daripada yang disimpan dengan plastic klip HDPE (21 hari). Cabai merah yang tidak dikemas dan disimpan pada suhu ruang hanya dapat disimpan sampai 6 hari. Kata Kunci : Capsicum anuum, Cold storage, Packaging